Peranan Konseling Dalam pemberian bantuan Pada Ranah Kepolisian - Mona; Margaretha Tri Astuti; Nur Aliza; Yeni Juwita; Daniel Ade. K; Affan Yusra (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The counseling process itself is needed to carry out a health examination that includes mental, as well as physical, a focus on well-being which is recommended to reduce the stigma of consultation for problems, benefiting the individual directly; make financial savings for the organization (eg, reducing sick absenteeism); and reduce absenteeism pressure on other staff. The research method that will be used in this case is a literature review where through the Google Scholar database using the keywords "Counseling in the Police", "Counseling", and "Police". Based on the results of the research above, it can be seen that the police, like the general public, have both physical and psychological health which can also be disturbed. The provision of counseling, training and leadership for the police needs to be improved for the better and is mandatory for every member of the police force. This is said because in the world of work in the police, of course, every member has memories or experiences incidents that can damage the personal of the police indirectly. It can be concluded that not only in the world of health, public, education and others who need counseling, but the police also need the role of counselors who help them counseling in solving problems experienced by each member of the police force.